Who believes in angels? [compact disc] - John, Elton; Carlile, Brandi (Interscope, 2025)
Written and recorded over twenty days; this album is a collaborative studio album between Elton John and Brandi Carlile. It mixes Elton-led songs and Brandi-led songs, with long-term collaborator Bernie Taupin and Brandi both contributing lyrics, and producer and co-writer Andrew Watt acting as the producer, mediator and creative conduit. They are backed by a world-class band of musicians comprising of Chad Smith, Pino Palladino and Josh Klinghoffer.